Pengembangan Game Moral Anak Berbasis Web sebagai Upaya Pendidikan Moral Anak - Ade Eman Supratman; M. Iman Wahyudi; Sopiullah Sopiullah (Jurnal Studi Gender dan Anak, 2022)
Children are future assets that will continue the life of a family. The emergence of various impacts of technological sophistication on the moral behavior of students, requires attention and supervision from various parties, research results (Nurlaela, 2017) and (Lu'luatuz Zuafah, Kiswoyo, 2021) shows that there is a higher negative impact than the positive impact. The negative impact caused is that the emotional level of students increases and difficult to control, loses track of time, becomes dishonest, does not care about the surrounding environment, interferes with student health, and students become lazy and often neglect other important activities. This study uses the Development Research method or also known as Research and Development (R&D), the results of expert validators in the context of developing this application are 81.25% with appropriate criteria, so that the development of this application is concluded to be suitable for use as one of the efforts of children's moral education, this application still needs further development both in terms of content, design and existing convenience.